An Interpretation of the Qur'an : English Translation of the Meanings. - Fakhry, Majid (NYU Press, 2015)
This new bi-lingual translation of the Qur'an is the only edition approved by Al-Azhar University in Cairo and offers followers of Islam a fluent and contemporary interpretation of this important text.